Interaction of fibrinogen and muramidase-released protein promotes the development of Streptococcus suis meningitis - Wang, Junping; Kong, Decong; Zhang, Shengwei; Jiang, Hua; Zheng, Yuling; Zang, Yating; Hao, Huaijie; Jiang, Yongqiang (Frontiers in Microbiology, 2015)
Muramidase-released protein (MRP) is as an important virulence marker of Streptococcus suis (S. suis) serotype 2. Our previous works have shown that MRP can bind human fibrinogen (hFg); however, the function of this interaction in S.suis meningitis is not known. In this study, we found that the deletion of mrp significantly impairs the hFg-mediated adherence and traversal ability of S. suis across human cerebral microvascular endothelial cells (hCMEC/D3). Measurement of the permeability to Lucifer yellow in vitro and Evans blue extravasation in vivo show that the MRP-hFg interaction significantly increases the permeability of the blood-brain barrier (BBB). In the mouse meningitis model, wild type S. suis caused higher bacterial loads in the brain and more severe histopathological signs of meningitis than the mrp mutant at day 3 post-infection. Western blot analysis and immunofluorescence observations reveal that the MRP-hFg interaction can destroy the cell adherens junction protein p120-catenin of hCMEC/D3. These results indicate that the MRP-hFg interaction is important in the development of S. suis meningitis.